Etnografi dan Geneologi Pelangkahan dalam Budaya Melayu Palembang - Nilawati, Nilawati; Muhajirin, Muhajirin; Jamil, Syahril; Abdillah, Muhammad; Amaliyah, Tiara (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
This study examines the pelangkahan tradition in the Malay community of Palembang using ethnographic and genealogical approaches, focusing on its cultural meanings and the dynamics of social change that influence it. This qualitative research uses participant observation, in-depth interviews, and documentation studies. Data are analyzed interpretively to understand the practices and meanings of pelangkahan from the perspectives of cultural actors, as well as to trace its origins and shifts in meaning over time. The findings indicate that pelangkahan functions to maintain family harmony, reinforce age hierarchy, and reproduce values of propriety and respect. However, modernization, education, and urbanization have contributed to a shift in pelangkahan from a binding customary obligation to a more flexible and symbolic practice. This study concludes that pelangkahan is a dynamic and adaptive tradition continuously negotiated within the interplay of custom, religion, and contemporary social realities.